MAT517 – Computational Linear Algebra February 2021 - PPSM, Pusat Pengajian Sains Matematik (Pusat Pengajian Sains Matematik, 2021)
Please check that this examination paper consists of FOUR (4) pages of printed material before you begin the examination. Instructions : Answer FOUR (4) questions.